Social disability of Brazilian mood disorder patients - Tucci, A.M. (2004)
Mood disorders cause many social problems, often involving family relationships. Few studies are available in the literature comparing patients with bipolar, unipolar, dysthymic, and double depressive disorders concerning these aspects. In the present study, demographic and disease data were collected using a specifically prepared questionnaire. Social adjustment was assessed using the Disability Adjustment Scale and family relationships were evaluated using the Global Assessment of Relational Functioning Scale. One hundred patients under treatment for at least 6 months were evaluated at the Psychiatric Outpatient Clinic of the Botucatu School of Medicine, UNESP. Most patients were women (82%) more than 50 (49%) years old with at least two years of follow-up, with little schooling (62% had less than 4 years), and of low socioeconomic level. Logistic regression analysis showed that a diagnosis of unipolar disorder (P = 0.003, OR = 0.075, CI = 0.014-0.403) and dysthymia (P = 0.001, OR = 0.040, CI = 0.006-0.275) as well as family relationships (P = 0.002, OR = 0.953, CI = 0914-0.992) played a significant role in social adjustment. Unipolar and dysthymic patients presented better social adjustment than bipolar and double depressive patients (P < 0.001), results that were not due to social class. These patients, treated at a teaching hospital, may represent the severest mood disorder cases. Evaluations were made knowing the diagnosis of the patients, which might also have influenced some of the results. Social disabilities among mood disorder patients are very frequent and intensive.